LEGAL ANALYSIS OF INDONESIA’S DECISION TO RELOCATE ITS CAPITAL TO EAST KALIMANTAN - Faiz Orlando Amryanto Pidani; Maria Puspita Dewi Sinaga; Sharon Pinkan Karwur; Zanneta Angkumala Putri Sandra (Problematika Hukum, 2020)
The relocation of the capital city of Indonesia from DKI Jakarta to East Kalimantan has been a major focus since it was announced by President Joko Widodo on August 16, 2019. This decision is rooted in population density, efforts for economic equality, and balanced development. This article deeply analyzes the driving factors and impediments behind this relocation, summarizes Indonesia's constitutional system perspective regarding the plan, and evaluates the feasibility of Indonesia in executing the capital city's relocation. This decision also has stirred varied responses in society, prompting the urgency for appropriate legislative revisions or even a referendum to ensure the right decision, impacting public trust. Using the literature review research method, this article extracts information from various legal sources such as books, journals, and related articles. A descriptive approach is employed to provide a systematic overview of the research object. Despite the pros and cons surrounding this relocation, the government has ratified Law No. 3 of 2022 concerning the State Capital to proceed with the plan.Keywords: Law, Capital City, Constitutional System, Public trust, Disaster